2010
DOI: 10.1093/mp/ssp120
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phosphate Starvation Responses in Plants: Signaling Players and Cross-Talks

Abstract: Phosphate (Pi) availability is a major factor limiting growth, development, and productivity of plants. In both ecological and agricultural contexts, plants often grow in soils with low soluble phosphate content. Plants respond to this situation by a series of developmental and metabolic adaptations that are aimed at increasing the acquisition of this vital nutrient from the soil, as well as to sustain plant growth and survival. The development of a comprehensive understanding of how plants sense phosphate def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
283
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(294 citation statements)
references
References 130 publications
5
283
0
6
Order By: Relevance
“…Indeed, in Arabidopsis, the in vivo role of these overexpressors seems more directly linked to the degradation of PCho and PEth polar heads, the by-products of phospholipid degradation triggered in response to Pi starvation. We have demonstrated that their induction is largely under the control of PHR1/PHL1, adding them to the list of proteins involved in lipid metabolism under the control of these transcription factors (Rouached et al, 2010;Pant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in Arabidopsis, the in vivo role of these overexpressors seems more directly linked to the degradation of PCho and PEth polar heads, the by-products of phospholipid degradation triggered in response to Pi starvation. We have demonstrated that their induction is largely under the control of PHR1/PHL1, adding them to the list of proteins involved in lipid metabolism under the control of these transcription factors (Rouached et al, 2010;Pant et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, tomato plants overexpressing LePS2;1 (homologous to PPsPase1 and PECP1) were reported to display altered Pi content, increased anthocyanin production, and enhanced acid phosphatase activity under Pi-rich conditions (Baldwin et al, 2008). To verify this hypothesis, we quantified the induction of several robust markers of Pi starvation responses (Duan et al, 2008;Rouached et al, 2010;Thibaud et al, 2010), including known players involved in Pi uptake and lipid remobilization (PHT1;4, SPX1, MGD2, MGD3, SQD1, and SQD2), and compared them to the expression level in their respective controls (wild type, low or high Pi). The triple KO mutants ( Fig.…”
Section: Ppspase1 and Pecp1 Are Dynamic Markers Of Pi Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…H. prostrata is restricted to low-P environments. It is thus likely that the P-starvation response that is well documented in other plants would never be triggered under natural low-P conditions in H. prostrata and that regulatory components found in plants such as Arabidopsis and rice (Oryza sativa; Rouached et al, 2010;Lin et al, 2014) have been attenuated or lost. This possibility is supported by the absence of orthologs in the H. prostrata transcriptome database for many lipid genes that are induced by the myeloblastosis transcription factor PHOS-PHATE STARVATION RESPONSE1 in response to Pi limitation in Arabidopsis (Bustos et al, 2010;AcevedoHernĂĄndez et al, 2012).…”
Section: The P Responsiveness Of Regulatory Network Is Reduced In Hmentioning
confidence: 99%
“…Achieving this objective necessitates a better understanding of how crops regulate P homeostasis. During the last decades, our knowledge on the molecular regulation of P transport and P redistribution in different plant organs during vegetative phase has progressed mainly in model plants such as Arabidopsis thaliana (for review, [17]). However, limited progress was achieved in crops such as wheat, a major dietary source of calories and protein for humans.…”
Section: Introductionmentioning
confidence: 99%